Simulation training for lobectomy: a review of current literature and future directions. (17th August 2018) - Nashaat, Abraham; Sidhu, Harsimranjit Singh; Yatham, Swetha; Al-Azzawi, Mohammed; Preece, Ryan
Abstract: With growing work-time restrictions and public expectations, the Halstedian educational model of 'see one, do one, teach one' is unfit for the modern training of thoracic residents. With the cardiothoracic surgical workforce set to decline by 50% over the next 10 years, new models are desperately needed to help trainees bypass the early error-prone phase of the lobectomy learning curve. In this review, we detail the development and validation of numerous simulators designed to teach trainees an array of skills ranging from basic technical skills to more complex non-technical skills. Given the recent increases in minimally invasive lobectomies, we critique both open and thoracoscopic simulators. We elucidate that whilst there are a growing number of thoracic simulators of varying fidelity available, fundamentally, there is currently a significant lack of well-designed trials validating various simulators for teaching lobectomy despite an awareness of their potential to improve surgical education. Furthermore, there is a void in the simulation training of non-technical skills within thoracic surgery. Encouragingly, there is a definite awareness of the ability of simulation to aid with the training of future thoracic surgical trainees.